(untitled) (SIRJANĀ – A Journal Of Arts and Art Education, 2023)
Vajrayāna Buddhism is a product of a new wave of thoughts amalgamated in the established practice of Buddhist religion. Every word coined are representative of the fresh air of creative thoughts presented for the practitioners of the promising religion to liberate the mankind in the existing life itself. Based on the philosophy originally propounded, it attempts to reach the height of glory in a logical way full of reasoning and conviction. These words are the fundamentals of the vajrayāna religious structure and the vajrayāna religious practice or carya.